A small, portable RNA device for the control of exon skipping in mammalian cells. Issue 8 (6th February 2018) - Vogel, Marc; Weigand, Julia E; Kluge, Britta; Grez, Manuel; Suess, Beatrix
Abstract: Splicing is an essential and highly regulated process in mammalian cells. We developed a synthetic riboswitch that efficiently controls alternative splicing of a cassette exon in response to the small molecule ligand tetracycline. The riboswitch was designed to control the accessibility of the 3′ splice site by placing the latter inside the closing stem of a conformationally controlled tetracycline aptamer. In the presence of tetracycline, the cassette exon is skipped, whereas it is included in the ligand's absence. The design allows for an easy, context-independent integration of the regulatory device into any gene of interest. Portability of the device was shown through its functionality in four different systems: a synthetic minigene, a reporter gene and two endogenous genes. Furthermore, riboswitch functionality to control cellular signaling cascades was demonstrated by using it to specifically induce cell death through the conditionally controlled expression of CD20, which is a target in cancer therapy.